Long distance triathlon: demands, preparation and performance - Laursen, P. B. (Journal of Human Sport & Exercise, 2011)
The rise in worldwide popularity of long distance triathlon racing comes with it an increased interest into how to train and prepare optimally for such an event. This paper examines the physiologic and bioenergetic demands of long distance triathlon racing, including energy requirements, muscle damage consequences, thermoregulatory demands and water turnover rates. In response to these physiological challenges, the second part of the paper describes the training goals and race practices that may assist to minimize these disturbances, in turn, optimizing performance and health for the long distance triathlete. Some of these race strategies include appropriate pacing, ensuring adequate fluid and carbohydrate consumption, acclimating to the heat, and consuming caffeine in appropriate quantities.